L-DOPA Uptake in Astrocytic Endfeet Enwrapping Blood Vessels in Rat Brain - M. Y. Inyushin; A. Huertas; Y. V. Kucheryavykh; L. Y. Kucheryavykh; V. Tsydzik; P. Sanabria; M. J. Eaton; S. N. Skatchkov; L. V. Rojas; W. D. Wessinger (Parkinson's Disease)
Astrocyte endfeet surround brain blood vessels and can play a role in the delivery of therapeutic drugs for Parkinson’s disease. However, there is no previous evidence of the presence of LAT transporter for L-DOPA in brain astrocytes except in culture. Using systemic L-DOPA administration and a combination of patch clamp, histochemistry and confocal microscopy we found that L-DOPA is accumulated mainly in astrocyte cell bodies, astrocytic endfeet surrounding blood vessels, and pericytes. In brain slices: (1) astrocytes were exposed to ASP+, a fluorescent monoamine analog of MPP+; (2) ASP+ taken up by astrocytes was colocalized with L-DOPA fluorescence in (3) glial somata and in the endfeet attached to blood vessels; (4) these astrocytes have an electrogenic transporter current elicited by ASP+, but intriguingly not by L-DOPA, suggesting a different pathway for monoamines and L-DOPA via astrocytic membrane. (5) The pattern of monoamine oxidase (MAO type B) allocation in pericytes and astrocytic endfeet was similar to that of L-DOPA accumulation. We conclude that astrocytes control L-DOPA uptake and metabolism and, therefore, may play a key role in regulating brain dopamine level during dopamine-associated diseases. These data also suggest that different transporter mechanisms may exist for monoamines and L-DOPA.